Cognitive Intervention Targeting Autobiographical Memory Impairment in Patients With Schizophrenia Using a Wearable Camera: A Proof-of-Concept Study - Dassing, Romane; Allé, Mélissa C.; Cerbai, Mathieu; Obrecht, Alexandre; Meyer, Nicolas; Vidailhet, Pierre; Danion, Jean-Marie; Mengin, Amaury C.; Berna, Fabrice (Frontiers in Psychiatry, 2020)
Autobiographical memory (AM) impairment in schizophrenia affects the richness of detail in personal memories and is one of the major predictors of patients’ social functioning. Despite the empirical evidence attributing these difficulties to a defective encoding process, cognitive remediation interventions targeting AM in schizophrenia often focus on the remote past, making it difficult to address the consequences of poor encoding. Our study evaluated the efficacy of an innovative approach using a wearable camera (NarrativeClip®) in reinforcing the encoding of recent daily life events in patients with schizophrenia. Seventeen patients with schizophrenia and 15 control participants wore the camera during four consecutive days. We evaluated two types of retrospective using the camera pictures: a simple visual retrospective and a visual retrospective associated with a specific event-cueing (VisR+EC). These two techniques were compared to a verbal retrospective and to the absence of retrospective. Our results showed that the VisR+EC allowed patients to retrieve as many details as the control group at a two-week interval. However, patients’ memories remained impaired when a simple visual or a verbal retrospective was used. Our study provides encouraging results to foster the use of a wearable camera in individualized cognitive remediation programs for AM impairment in schizophrenia.